Productivity of Forages in Grassland Merapi Post-Eruption Area, Sleman, Yogyakarta, Indonesia - Umami, Nafiatul; Suhartanto, Bambang; Suwignyo, Bambang; Suseno, Nilo; Fenila, Sarah Adrian; Fajarwati, Ruslina (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2015)
This research aimed to investigate the productivity and quality of forages (including dry matter, organic matter, crude fiber, crude protein, and extract ether) in the area of Kali Kuning and Krasak River. This area was affected by Mount Merapi Eruption on 2010. The data were taken from the area around the river due to the area was found to be firstly revegetated after the eruption. The Forage classified as grass, legume and forbs. The method applied in the research was Line Intercept method which was done by seeing the botanical composition there and was performed at several observation points. The forage was taken as the sample and then calculated its production and proximately analyzed to determine its chemical composition. The results showed that around the river, the widest cover area in 2013 and 2014 was Brachiariabrizantha grasses. The largest dry matter production in 2013 was Pennisetumpurpuphoides as much as 165.57 g mâ2, while in 2014 the largest production of DM was Brachiariabrizantha as much as 190.37 g mâ2. Frobs with another type of weed also spread in this area. The Quality of forages around Krasak River increased in 2014 due to the addition of organic matter contained in the soil and the minerals weathering from year to year.